Competency of Shariah Auditors in Malaysia: Issues and Challenges - Ali, Nor Aishah Mohd; Mohamed, Zakiah Muhammadun; Shahimi, Shahida; Shafii, Zurina (Journal of Islamic Finance, 2015)
Over the last decade since the inception of the first Islamic bank in Malaysia in 1983, Malaysia saw an increasing demand for Islamic banking services from consumers.Â  Whilst the need for highly trained and skilled manpower in the Islamic banking industry is well established, the main challenge is really a mismatch of talent pool between what is required by the banks and what is offered by the market. Thus, this paper argues for a competency framework for shariah auditors in Malaysia. Prior research reveals that the competency requirements for shariah auditors were still not developed even though there is a need for it. A more recent empirical study reveals that most shariah auditors are either trained in shariah or auditing discipline. There is indeed an urgent need to draft the competency requirements which will include the knowledge, skills and other characteristics (KSOC) requirements to ensure adequate supply of competent shariah auditors to meet the expanding market demand. This paper proposes a new KSOC model as a basis for competency framework for shariah auditors that can uphold their effective functioning in our Islamic banking system.